Project Portfolio Management : a View from the Management Trenches. (John Wiley & Sons, 2011)
"Portfolio management is critically important, but often quickly dismissed as unnecessary 'strategy overhead'. Applied in the right ways, with the right level of discipline, it can be an extremely insightful lens through which to see untapped sources of business value. Credit to the authors for shedding much needed light on both the art and science of project portfolio management, both strategic and operational."--Matt Wagner, Director, Strategy & Planning, Hewlett-Packard "This is one of the most straightforward and easy to read books on Portfolio Management. It contains simple and relevant examples of how to organize and execute a PM process that will satisfy senior leadership's needs while streamlining the information and processes that are supported by the 'trenches'."--Christine Cioffe, Vice President, Enterprise-wide Portfolio Management Merck & Co., Inc "Project Management has been hailed as the foundation of modern business, but managing the organization's entire portfolio of projects carries this discipline to the next level. Based on a wealth of hard-won experience, this book offers no-nonsense guides that can turn your organization into an enterprise-wide system for managing R & D programs, product launches, IT systems, new facilities, mergers, PR programs, change efforts, and any of the myriad other activities that challenge leaders in all walks of life. Essential reading."--William E. Halal, PhD Professor Emeritus of Science, Technology, & Innovation George Washington University, President, TechCast LLC "'Project Portfolio Management' provides valuable guidance on how organizations can optimize the return from their investments in change - not least in balancing process with the equally important dimensions of governance and changed behaviors." -John Suffolk, HM Goverrnment CIO "In order to 'run IT as a business', it is.